Rancang Bangun Aplikasi E-register International Conference Berbasis Online Pada Universitas Lancang Kuning - Febriadi, Bayu; Putra, Pandu Pratama (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Computer-based information systems are very influential in the world of work, as well as web-based information systems are used as a means of information enhancement. Utilization will facilitate a job as well as faster data processing, the decision to be taken more precisely, saving time and cost. Because the needs of the yellowish university to realize the vision and mission must be in line with the activities undertaken, one of them by producing a paper or a scientific paper lecturer who indexed such as scopus and thompson, so the yellowish university held an international Conference held in cooperation with other universities, both domestic and foreign, this requires a media or information that can be accessed by lecturers in the country and abroad in terms of registration of scientific work to be on international Conference activities with online-based. In the international Conference that will be held university of lancang kuning no media that can be used as a means to promote, because this is considered very important for the achievement of the purpose of international Conference activities to be implemented. The method used by collecting existing data and analyzing problems in the collection and adjustment of Paper International Conference. The general purpose of this research is to build an E-register paper application to make it easier for users to register papers for seminars at youthful university.